First-Principles Calculations of Stable Geometric Configuration and Thermodynamic Parameters of Cadmium Sulfide Thin-Film Condensates - Oleksyn, Z.; Naidych, B.; Chernikova, O.; Glowa, L.; Ogorodnik, Y.; Solovyov, M.; Vashchynskyi, V.; Yavorskyi, R.; Il’chuk, G. (Physics and Chemistry of Solid State, 2021)
Thin-film CdS layers obtained by the open evaporation method in vacuum are considered and cluster models for calculation of crystal, band structure and thermodynamic parameters are proposed. The thermodynamic parameters of the formation energy ΔE, enthalpy of formation ΔH, Gibbs energy ΔG, entropy ΔS and specific heat capacities at constant pressure and volume for cubic and hexagonal crystallographic modifications are determined. The stable crystal structure for cadmium sulfide was determined from the analysis of Gibbs energy temperature dependences for the sphalerite and wurtzine phases.